The effect of Phyllanthus taxodiifolius beille extracts and its triterpenoids studying on cellular energetic stage of cancer cells - Patiwat Sakkrom (2018)
Problem statement: The Multidrug Resistance phenomenon (MDR) is the cause of unsuccessful in cancer chemotherapy. The tradition plant is the population used as the alternative medicine in cancer therapy. Due to, P. taxodiifolius is medicinal Thai plant which is used as diuretic drug which has never been explored as the anticancer activities. Approach: Air-dried powder of P. taxodiifolius leaves and twigs were serially extracted by hexane, ethyl acetate, acetone and methanol. These four extracts were tested the antiproliferative activity on four cancer cell lines. These results lead to successively purify two triternoids that are glochidone (1) and lupeol (2). Both pure compounds were tested the anticancer properties on same cancer cell lines and further investigate the cellular energetic state perturbation by measuring the mitochondrial membrane potential modification. Results: Four crude extracts were extracted and two triterpenoids (glochidone and lupeol) were purified and identified from hexane extract. Our antiproliferative activity of both compounds respectively showed in the IC50value of K562, K562/Adr, GLC4 and GLC4/Adr equal to 2.2±0.6, 4.2±1.5. 3.1±1.0 and 3.2±0.9 μg mL-1for glochidone and 2.3±0.6, 4.5±1.7, 2.3±0.5 and 2.6±0.5 μg mL-1for lupeol. The R value, which represents the multidrug resistance phenotype, is about 2 for P-glycloprotein overexpression in K562/Adr and 1 for MRP1 overexpression in GLC4/Adr. Conclusion: All crude extractions and two triterpenoids show the clear evidence of anticancer activity of both sensitive and resistance of erythroleukemic and Small cell lung cancer cell lines. Both compounds are not recognized by ABCB1 and ABCC1 proteins. Our results also indicated that lupeol initiate cell death by mitochondria membrane potential modification specially the sensitive cell line. © 2010 Science Publications.